2019
DOI: 10.1002/term.2915
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adiponectin secreted from adipose‐derived stem cells on bone‐fat balance and bone defect healing

Abstract: The efficacy of adiponectin (APN) in regulating bone metabolism remains controversial. This study aimed to investigate the role of APN secreted from adipose-derived stem cells on adipogenesis and osteogenesis. Human APN gene was transfected via recombinant adenovirus into adipose derived stem cells (ASCs) in vitro and were cocultured with bone marrow mesenchymal stem cells (BMSCs) in using a transwell chamber. Adipogenesis was inhibited in APN-transfected ASCs; in BMSCs, adipogenesis was inhibited, but osteoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…ACRP30, also referred to as adiponectin, is the most abundant adipocytokine secreted by adipocytes and plays a pivotal role in glucose metabolism and energy homeostasis [ 34 , 35 ]. Although ACRP30 influences the proliferation of hASCs, it is also linked to adipocyte and osteoblast differentiation: an increase of ACRP30 mRNA expression and protein secretion have been observed in hASCs during their differentiation into osteoblast [ 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…ACRP30, also referred to as adiponectin, is the most abundant adipocytokine secreted by adipocytes and plays a pivotal role in glucose metabolism and energy homeostasis [ 34 , 35 ]. Although ACRP30 influences the proliferation of hASCs, it is also linked to adipocyte and osteoblast differentiation: an increase of ACRP30 mRNA expression and protein secretion have been observed in hASCs during their differentiation into osteoblast [ 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fabricated synthetic vascular grafts from PGS core and electrospun PCL shell have also been reported in several studies using a combination of electrospinning and salt leaching. [ 21,102,181,182 ] These acellular grafts degraded rapidly and supported the regeneration of neoarteries nearly free of foreign body reaction in rat abdominal aorta. [ 21 ] To enhance mechanical properties suitable for human application, the thickness of the PCL sheath was increased, which significantly reinforced the whole grafts.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Later, the superiority of PGS/PCL grafts over autologous jugular vein grafts was observed regarding the reconstruction of the carotid artery. [ 182 ] The comparison showed that PGS/PCL grafts were remodeled into neoarteries with smooth and even vessel wall comparable to native carotid arteries within 12 months after implantation, whereas autologous grafts remodeled into neoarteries with dilated vessel cavity and thickening of the vessel wall. Additionally, in PGS/PCL neoarteries, muscular components were well organized, and fibers with higher flexibility and elasticity were observed.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Immunoblots were performed as we previously described. 2 Treated cell samples were lysed with RIPA lysis buffer for around 30 min on ice. Antibodies used for immunoblot were listed in Table S2.…”
Section: Rna Extraction Rt-pcr Analysis and Immunoblottingmentioning
confidence: 99%